2017
DOI: 10.1073/pnas.1614075114
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into the activation mechanism of dynamin-like EHD ATPases

Abstract: Eps15 (epidermal growth factor receptor pathway substrate 15)-homology domain containing proteins (EHDs) comprise a family of dynamin-related mechano-chemical ATPases involved in cellular membrane trafficking. Previous studies have revealed the structure of the EHD2 dimer, but the molecular mechanisms of membrane recruitment and assembly have remained obscure. Here, we determined the crystal structure of an amino-terminally truncated EHD4 dimer. Compared with the EHD2 structure, the helical domains are 50°r ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
81
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(85 citation statements)
references
References 36 publications
(45 reference statements)
4
81
0
Order By: Relevance
“…S7A, Bottom Right). The proposed reorientation is in agreement with the crystal structure of the structurally related N-terminally deleted EHD4 (29). The described conformational change allows the N terminus of EHD2 to be inserted into the lipid layer.…”
Section: Discussionsupporting
confidence: 84%
“…S7A, Bottom Right). The proposed reorientation is in agreement with the crystal structure of the structurally related N-terminally deleted EHD4 (29). The described conformational change allows the N terminus of EHD2 to be inserted into the lipid layer.…”
Section: Discussionsupporting
confidence: 84%
“…Eps15‐homology domain‐containing proteins (EHDs) are often included in the dynamin superfamily owing to their micromolar affinities for nucleotides, self‐assembly, stimulated hydrolysis, and roles in membrane remodeling events . Furthermore, the helical bundle adjacent to the G domain undergoes a significant conformational change, similar to dynamins in general . However, while the EHD catalytic core adopts a G domain fold, these enzymes specifically bind and hydrolyze ATP, rather than GTP, due to a steric occlusion in their nucleotide binding pockets …”
Section: Strays Waifs and Wannabes: An Existential Crisis Of What Dementioning
confidence: 99%
“…Accessibilities of the spin labels to O 2 and NiEDDA further supported the notion that this region of the helical domain inserts into the membrane [10]. A subsequent study [117] found that this membrane binding region also included additional amino acids in the tip region, as the helical domain can undergo a domain rotation that allows additional amino acids to come into contact with the membrane (Fig. 7).…”
Section: Non-amyloidogenic Proteins and Membrane Remodelingmentioning
confidence: 61%
“…7). Using SDSL and EPR we tested whether this region was responsible for recruiting EHD2 to the membrane [10, 117]. First, the three native cysteines in EHD2 were mutated to serines.…”
Section: Non-amyloidogenic Proteins and Membrane Remodelingmentioning
confidence: 99%